ANALISIS DAMPAK KENAIKAN EKSPOR TEMBAKAU INDONESIA TERHADAP BEACUKAI NEGARA - Adrian Permana; Dwi Khaira Ramdhanni; Ricky Firmansyah (Melati Institute, 2023)
Indonesia is one of the world's main tobacco producers and is also a major tobacco exporter. The recent increase in Indonesia's tobacco exports has had a significant impact on the customs revenues of the destination countries. This study examines the impact of Indonesia's increasing tobacco exports on the customs revenues of the destination countries based on a literature review. The research method used is a literature review, collecting data from journals, books, and other related documents. The results show that the increase in Indonesia's tobacco exports can affect the customs revenues of destination countries, especially if the destination countries have different tax policies. The increase in tax rates on tobacco products imposed by destination countries can affect the selling price and market demand. Nevertheless, the increase in Indonesia's tobacco exports also has a positive impact on the welfare of society and economic growth. However, the increase in tobacco production can also have negative impacts on public health, including increasing the risk of tobacco-related diseases. Therefore, the Indonesian government needs to formulate appropriate and effective policies to address the changes in the global market. This literature review can serve as a basis for further research on the impact of Indonesia's increasing tobacco exports and